Association between vascular endothelial dysfunction and stroke incidence in the general Japanese population: Results from the tohoku medical megabank community-based cohort study - Harutomo Numazaki; Takahito Nasu; Mamoru Satoh; Yuka Kotozaki; Kozo Tanno; Koichi Asahi; Hideki Ohmomo; Atsushi Shimizu; Shinichi Omama; Yoshihiro Morino; Kenji Sobue; Makoto Sasaki (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2023)
Background: Flow-mediated dilation (FMD) measures vascular endothelial function by evaluating the vasodilatory response of blood vessels to increased blood flow. Nevertheless, the association between FMD and stroke incidence in a general population remains unclear. This study investigated the association between vascular endothelial function and stroke incidence in the general Japanese population. Methods: Based on cohort data from the Tohoku Medical Megabank Community-based Cohort Study, participants aged ≥18 years were recruited from Iwate Prefecture, with the final sample comprising 2952 subjects. Results: The FMD level was 0.5%–27.1%, with a median of 5.0% (interquartile, 4.2%–11.3%). The mean follow-up period was 5.5 ± 1.8 years (range, 0.6–6.9 years). After dividing the participants into two subgroups according to the median FMD value, a multivariate Cox regression analysis adjusting for gender, age, smoking, alcohol consumption, systolic blood pressure, low-density lipoprotein cholesterol, estimated glomerular filtration rate, N-terminal pro-brain natriuretic peptide, high-sensitivity cardiac troponin T and hemoglobin A1c revealed that a lower FMD value was strongly associated with incidences of total stroke (hazard ratio[HR] = 2.13, 95% confidence interval[CI] = 1.48–3.07, p < 0.001), ischemic stroke (HR = 3.33, 95%CI = 2.00–5.52, p < 0.001), nonlacunar stroke (HR = 2.77, 95%CI = 1.49–5.16, p = 0.001), and lacunar stroke (HR = 5.12, 95%CI = 1.74–16.05, p = 0.003). Conclusions: This study showed that a low FMD value might reflect vascular endothelial dysfunction and then was associated with ischemic stroke incidence in the general Japanese population, suggesting that FMD can be used as a tool to identify future stroke risk.